The macrophage activation marker CD163 is associated with IL28B genotype and hepatic inflammation in chronic hepatitis C virus infected patients. Issue 4 (10th November 2015) - Dultz, G.; Gerber, L.; Zeuzem, S.; Sarrazin, C.; Waidmann, O.
Summary: Recent data highlighted the association of the macrophage activation marker CD163 with histological inflammation and fibrosis in chronic hepatitis C virus (HCV) infection. The aim of this study was to investigate the influence of successful antiviral treatment and IL28B genotypes on macrophage activation reflected by CD163 levels in HCV infected patients. In a retrospective cohort study, serum sCD163 levels were correlated with results of liver histopathology, IL28B genotyping and clinical parameters in 329 patients with HCV infection, 15 healthy controls and in 161 patients who achieved a sustained virologic response after antiviral treatment. sCD163 levels were significantly higher in patients with chronic HCV infection in comparison to healthy controls (5202 vs 896 ng/mL, P < 0.001). In the multivariate logistic regression analyses, sCD163 was independently associated with histologically determined inflammation ( P = 0.043) but not with fibrosis ( P = 0.091). sCD163 dropped significantly after successful antiviral treatment in comparison to baseline values (5202 vs 3093 ng/mL, P < 0.001). In the univariate analyses, sCD163 was significantly associated with IL28B genotype (C/C vs C/T+T/T) with higher values in the C/C group (6098 vs 4812 ng/mL, P = 0.003). In the multivariate logistic regression model, sCD163 levels were significantly associated with IL28B genotype ( P = 0.003) and sustained virologic response (SVR) ( P < 0.001). Our data support the association of activated liver macrophages with hepatic necroinflammation in chronic HCV infection as sCD163 levels drop rapidly after SVR. The irresponsiveness of IL28B minor genotypes to interferon might be related to a lower level of macrophage activation in these patients.